Has the Global Banking System Become More Fragile over Time? - Anginer, Deniz; Demirgüç-Kunt, Asli (2012)
This paper examines time-series and cross-country variations in default risk co-dependence in the global banking system. The authors construct a default risk measure for all publicly traded banks using the Merton contingent claim model, and examine the evolution of the correlation structure of default risk for more than 1,800 banks in more than 60 countries. They find that there has been a significant increase in default risk co-dependence over the three-year period leading to the financial crisis. They also find that countries that are more integrated, and that have liberalized financial systems and weak banking supervision, have higher co-dependence in their banking sector. The results support an increase in scope for international supervisory co-operation, as well as capital charges for "too-connected-to-fail" institutions that can impose significant externalities.